Role of diagnostic hysteroscopy in abnormal uterine bleeding and its histopathological correlation - Prashant Bhingare; Sanjaykumar Pagare; Shrinivas Gadappa; Rahul Ashok Ingle (Barpeta Obstetrics and Gynaecological Society, 2021)
Objectives: This study has been taken up to analyze the role of hysteroscopy in the evaluation of abnormal uterine bleeding (AUB) in terms of accuracy of hysteroscopic findings and contribution of the procedure to clinical diagnosis Methods: Prospective observational study at a tertiary care hospital in women undergoing dilatation & curettage for gynaecological complaints. Results: 50 Patients who presented with AUB underwent panoramic hysteroscopy and subsequent dilatation and curettage (D & C). Most common age group was 40-49yrs (52%). Most of the patients (56%) had symptoms for 6 months to 1 year and most common presenting symptom was menorrhagia (82%) and polymenorrhea (10%). Hysteroscopy reported 30 patients (60%) as negative view and 20 patients (40%) as abnormal view. The sensitivity, specificity, PPV and NPV for hysteroscopy was 95.23 %, 100 %, 100 % and 96.66 % respectively and for D&C was 61.9 %, 100 %, 100% and 78.37 % respectively. In the present study, in 82% patients; the results of hysteroscopy and curettage were in agreement. Conclusion: Hysteroscopy is a safe, reliable and quick procedure in the diagnosis of cases with abnormal uterine bleeding with high sensitivity, specificity and negative predictive value.